2019
DOI: 10.1088/1755-1315/273/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Autocorrelation of Earthquake Magnitudes in Tripa Fault, Aceh Province, Indonesia

Abstract: The position of Aceh coincides with the fault zone along the Bukit Barisan called Sumatran Fault. The Tripa Fault is marked by the mountainous area and the trajectory of the Kuala Tripa and Meureubo Rivers along 180 km. Tripa faults are categorized as active faults indicated by the occurrence of several destructive earthquakes in the region. One effort that can be done to reduce the negative impacts caused by the earthquake disaster is to make predictions by mapping the occurrence of earthquakes. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…To identify statistically significant patterns in seismic activity data, a series of analyses employing four distinct techniques was conducted. These methods have been effectively utilized in numerous studies across the globe, including Romania [29], Indonesia [30], the Red Sea [14], China [31], and Pakistan [32]. It has consistently yielded valuable insights into areas of heightened seismic activity, spatial configurations of earthquake events, and the spatiotemporal dynamics, mechanisms, and characteristics of seismic activity [33].…”
Section: Related Work and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…To identify statistically significant patterns in seismic activity data, a series of analyses employing four distinct techniques was conducted. These methods have been effectively utilized in numerous studies across the globe, including Romania [29], Indonesia [30], the Red Sea [14], China [31], and Pakistan [32]. It has consistently yielded valuable insights into areas of heightened seismic activity, spatial configurations of earthquake events, and the spatiotemporal dynamics, mechanisms, and characteristics of seismic activity [33].…”
Section: Related Work and Methodologymentioning
confidence: 99%
“…Spatial autocorrelation is an important index to express the spatial behavior of geographical elements, reflecting the interdependence between some elements in the study area [30]. The global indicators of spatial association, such as Global Moran's I, and the Local Indicators of Spatial Association (Local Moran's I, also known as LISA), are frequently employed to quantify spatial autocorrelation [33].…”
Section: Global and Local Moran's Imentioning
confidence: 99%
“…In the proposed approach in this study, it is stated that the ROC-based Gini coefficient is an effective and efficient tool to measure the degree of aggregated space-time clustering. Spatial patterns of earthquakes magnitudes that occurred around the Tripa Fault in Aceh province between 1990-2017 were investigated by Sofyan et al (2019). As a result of this research, it was concluded that there is a relationship between the earthquake magnitudes globally in the Tripa fault region (Sofyan et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…Spatial patterns of earthquakes magnitudes that occurred around the Tripa Fault in Aceh province between 1990-2017 were investigated by Sofyan et al (2019). As a result of this research, it was concluded that there is a relationship between the earthquake magnitudes globally in the Tripa fault region (Sofyan et al, 2019).…”
Section: Introductionmentioning
confidence: 94%